Intermediate Accounting (Book). - Murray, Dennis; Hendrickson, Harvey S. (The Accounting Review, 1985)
Reviews the book "Intermediate Accounting," by Lanny G. Chasteen, Richard E. Flaherty and Melvin C. O'Connor.